2012
DOI: 10.1183/09031936.00052512
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal gastro-oesophageal reflux, asthma and symptoms of OSA: a longitudinal, general population study

Abstract: Nocturnal gastro-oesophageal reflux (nGOR) is associated with asthma and obstructive sleep apnoea (OSA). Our aim was to investigate whether nGOR is a risk factor for onset of asthma and onset of respiratory and OSA symptoms in a prospective population-based study.We invited 2640 subjects from Iceland, Sweden and Belgium for two evaluations over a 9-year interval. They participated in structured interviews, answered questionnaires, and underwent spirometries and methacholine challenge testing. nGOR was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 32 publications
2
47
0
6
Order By: Relevance
“…The association between new nighttime reflux and incident OSA symptoms was stronger in men, whereas the association between persistent nocturnal GERD and new respiratory symptoms was stronger in women. 138 These differences may be important in explaining some of the gender-related distinctions seen in other publications, which investigated the relationship between asthma and obesity or other comorbidities, leading again toward more specific and nuanced phenotypes and endotypes. In an analysis of the Busselton population study, 129 which compared the prevalence of nocturnal reflux symptoms in patients with untreated OSA, patients with OSA using CPAP therapy, and general population, GERD symptoms were found to be related to the presence and severity of OSA, whereas CPAP therapy decreased significantly the prevalence of reflux symptoms.…”
Section: The Other Inner Circle or Triangle Of Asthma Osa And Gerdmentioning
confidence: 97%
See 1 more Smart Citation
“…The association between new nighttime reflux and incident OSA symptoms was stronger in men, whereas the association between persistent nocturnal GERD and new respiratory symptoms was stronger in women. 138 These differences may be important in explaining some of the gender-related distinctions seen in other publications, which investigated the relationship between asthma and obesity or other comorbidities, leading again toward more specific and nuanced phenotypes and endotypes. In an analysis of the Busselton population study, 129 which compared the prevalence of nocturnal reflux symptoms in patients with untreated OSA, patients with OSA using CPAP therapy, and general population, GERD symptoms were found to be related to the presence and severity of OSA, whereas CPAP therapy decreased significantly the prevalence of reflux symptoms.…”
Section: The Other Inner Circle or Triangle Of Asthma Osa And Gerdmentioning
confidence: 97%
“…Interestingly, independent predictors of habitual snoring included GERD (OR, 2.1) and use of inhaled corticosteroids (OR, 2.6), whereas high OSA risk was predicted by asthma severity step (OR, 1.5), GERD (OR, 2.7), and use of inhaled corticosteroids (OR, 4.0). 56 A recent prospective study from northern Europe 138 found that individuals with persistent nocturnal reflux were approximately 2 times more likely to report incident asthma (adjusted OR, 2.3) and new onset of (daytime or nighttime) respiratory symptoms such as wheezing, dyspnea, chest tightness, or cough, when compared with participants who never had nocturnal reflux symptoms. Of note, in this study, OSA was assessed by self-reported symptoms and not by polysomnography.…”
Section: The Other Inner Circle or Triangle Of Asthma Osa And Gerdmentioning
confidence: 99%
“…El mecanismo fisiopatológico que fundamenta esta relación se basa en una dilatación transitoria del esfínter esofágico inferior, como consecuencia de un aumento de la presión intratorácica. Este aumento de la presión se debe a la obstrucción de la vía aérea superior secundaria a SAOS y al esfuerzo respiratorio aumentado con el fin de hacer resistencia a la obstrucción y permitir el flujo de aire para el intercambio gaseoso [32][33][34] . En un estudio que incluyó 2.640 pacientes, se encontró que pacientes con RGE tienen un OR de 2,2 (IC 1,3-3,6) de desarrollar SAOS 33 .…”
Section: Reflujo Gastroesofágico (Rge)unclassified
“…Este aumento de la presión se debe a la obstrucción de la vía aérea superior secundaria a SAOS y al esfuerzo respiratorio aumentado con el fin de hacer resistencia a la obstrucción y permitir el flujo de aire para el intercambio gaseoso [32][33][34] . En un estudio que incluyó 2.640 pacientes, se encontró que pacientes con RGE tienen un OR de 2,2 (IC 1,3-3,6) de desarrollar SAOS 33 . En otro estudio, se estudiaron a 18 pacientes con diagnóstico de SAOS y RGE, en los cuales se realizó de forma simultánea una pHmetría de 24 h de dos canales y polisomnografía.…”
Section: Reflujo Gastroesofágico (Rge)unclassified
“…LPR ist häufig assoziiert mit Schnarchen, da Reflux von Mageninhalt in Larynx und Pharynx entzündliche Reaktionen und hierdurch sensorische Defizite hervorruft, die auch für die Obstruktion der oberen Atemwege verantwortlich sein könnten. Insofern ist eine strenge Assoziation nicht verwunderlich[24], eine Kausalität wurde bislang nicht nachgewiesen und erscheint eher unwahrscheinlich. Fragebogen und Endoskopie.D die 24 h-pH-Metrie.…”
unclassified